Structure of the Arabidopsis JMJ14-H3K4me3 Complex Provides Insight into the Substrate Specificity of KDM5 Subfamily Histone Demethylases. Issue 1 (12th December 2017) - Yang, Zhenlin; Qiu, Qi; Chen, Wei; Jia, Bei; Chen, Xiaomei; Hu, Hongmiao; He, Kaixuan; Deng, Xian; Li, Sisi; Tao, W. Andy; Cao, Xiaofeng; Du, Jiamu
Abstract : The structure of the Arabidopsis JMJ14 catalytic domain in complex with H3K4me3 peptide reveals a conserved substrate binding mode shared by both plant and animal KDM5 subfamily histone demethylase. Abstract: In chromatin, histone methylation affects the epigenetic regulation of multiple processes in animals and plants and is modulated by the activities of histone methyltransferases and histone demethylases. The jumonji domain-containing histone demethylases have diverse functions and can be classified into several subfamilies. In humans, the jumonji domain-containing Lysine (K)-Specific Demethylase 5/Jumonji and ARID Domain Protein (KDM5/JARID) subfamily demethylases are specific for histone 3 lysine 4 trimethylation (H3K4me3) and are important drug targets for cancer treatment. In Arabidopsis thaliana, the KDM5/JARID subfamily H3K4me3 demethylase JUMONJI14 (JMJ14) plays important roles in flowering, gene silencing, and DNA methylation. Here, we report the crystal structures of the JMJ14 catalytic domain in both substrate-free and bound forms. The structures reveal that the jumonji and C5HC2 domains contribute to the specific recognition of the H3R2 and H3Q5 to facilitate H3K4me3 substrate specificity. The critical acidic residues are conserved in plants and animals with the corresponding mutations impairing the enzyme activity of both JMJ14 and human KDM5B, indicating a common substrate recognition mechanism for KDM5 subfamily demethylases shared by plants and animals and further informing efforts to design targeted inhibitors of human KDM5.